FAMILY CONTROL, BIAYA KEAGENAN DAN RISIKO KEUANGAN TERHADAP NILAI PERUSAHAAN - hilda mary (AKUNTANSI DEWANTARA, 2021)
The effect of family control, agency cost and financial risk on firm value in company listed on the IDX. Three independent variable this research is family control, agency cost and financial risk and dependendt variabel is company value, and control variable is propability. The sample of this research consisted 100 companies, and technique using rendom sampling method. The result this research indicate that family control has a negative and significant effect on firm value. Agency cost and financial risk do not effect the firm value. And probability has a positive and significant effect on firm value